The Adverse Reactions of Lianhua Qingwen Capsule/Granule Compared With Conventional Drug in Clinical Application: A Meta-Analysis - Hu, Caiyun; He, Bin; Gong, Fengfeng; Liang, Mingming; Zhao, Dongdong; Zhang, Guoliang (Frontiers in Pharmacology, 2022)
Objectives: Lianhua Qingwen capsule/granule (LHQW) is an innovative patented traditional Chinese medicine with potential curative effects on respiratory diseases. However, no consensus has been reached on the security of LHQW to date. The current meta-analysis was performed to evaluate the safety profile of LHQW in relation to conventional drugs (PROSPERO CRD-42020224180). Methods: Comprehensive document retrieval was performed from both English and Chinese databases. Results were reported as risk ratio (RR) with 95% confidence interval (CI). Subgroup, sensitivity and meta-regression analyses were conducted to explore the possible sources of heterogeneity across eligible studies. Results: In total, 217 experimental studies were included. For pooled studies, the incidence of adverse reactions was lower in the LHQW group than the conventional drug group (RR=0.63, 95% CI=0.58-0.69, P<0.001). In the evaluation of treating disease, significant reduced incidence of adverse reactions during treatment of influenza A (H1N1) and influenza were detected in the LHQW group. In the evaluation of security indexes, LHQW group has a reduced incidence of respiratory system damage, skin and its appendages injury, nervous system damage and gastrointestinal system damage, along with other adverse reactions. Subgroup analysis additionally revealed a reduced incidence of some adverse reactions in the LHQW group compared to the conventional drug group (Rash of skin and its appendage damage, dizziness or headache owing to nervous system damage, nausea or vomiting from gastrointestinal system damage and resurgence of disease from other adverse reactions). Conclusions: The current study provides potential a reference for the security of LHQW. Further long-term high-quality studies are essential to validate our conclusions.